DEVELOPMENT OF PRODUCTIVE VOCATIONAL PROGRAM LEARNING MODELS TO SHAPE THE ENTREPRENEURSHIP CHARACTER OF GRADUATES - Wawan Gunawan; Bambang Winarto; Hari Karyono (Institute of Computer Science (IOCS), 2022)
This study aims to produce a productive vocational program model to shape the entrepreneurial character of graduates. The design applied in this research is research and development. The results of the application of the research and development approach, in the areas of expertise in Technology and Engineering, Tourism, and Business and Management, can develop a productive vocational program learning model that includes three aspects, namely learning materials, learning methods, and evaluation of productive learning outcomes. Learning materials need to be designed by focusing on productive activities (making or creating products, both goods and services) that emphasize the entrepreneurial character, learning methods are assignment or project-work, and evaluation of learning outcomes needs to apply performance evaluation techniques by emphasizing process and product evaluation. Based on the results of the study, it is suggested: to ensure that vocational graduates enter DU/DI and work independently, it is necessary to be equipped with entrepreneurial productive competencies; and so that the learning outcomes of entrepreneurship can be put into real practice in DU/DI or starting a business, it is necessary to choose a learning model that is considered effective to be applied in learning.